(untitled) (International Journal of Environmental Sciences, 2025)
From burning with zeal to burnout and from fairness to being far away from it lies the well-being and satisfaction of the employees. Human resource of any organization plays a crucial role and are a critical asset for the organization. The satisfaction of the manpower is of utmost importance for the organization, because it also leads to higher productivity from them, which ultimately paves the path for organization’s success. The intention of this paper is to study, the major variables that affects the job satisfaction in an organizational setting is. Organizational justice and burnout are taken as an independent variables and job satisfaction is considered as a dependent variable. To know its impact, this study has been conducted. Data was collected through questionnaire. The sample was collected from 600 working employees from banking sector. The results clarified that organizational justice has a positive impact on job satisfaction. However, burnout has negative impact on job satisfaction. Moreover, it deeply studies impact of organizational justice and burnout with other aspects of job satisfaction. To the best of our knowledge the existing literature overlooked the impact of these two variables on job satisfaction.